Matching Energy Consumption and Photovoltaic Production in a Retrofitted Dwelling in Subtropical Climate without a Backup System - Sergio Gómez Melgar; Antonio Sánchez Cordero; Marta Videras Rodríguez; José Manuel Andújar Márquez (Energies, 2020)
The construction sector is a great contributor to global warming both in new and existing buildings. Minimum energy buildings (MEBs) demand as little energy as possible, with an optimized architectural design, which includes passive solutions. In addition, these buildings consume as low energy as possible introducing efficient facilities. Finally, they produce renewable energy on-site to become zero energy buildings (ZEBs) or even plus zero energy buildings (+ZEB). In this paper, a deep analysis of the energy use and renewable energy production of a social dwelling was carried out based on data measurements. Unfortunately, in residential buildings, most renewable energy production occurs at a different time than energy demand. Furthermore, energy storage batteries for these facilities are expensive and require significant maintenance. The present research proposes a strategy, which involves rescheduling energy demand by changing the habits of the occupants in terms of domestic hot water (DHW) consumption, cooking, and washing. Rescheduling these three electric circuits increases the usability of the renewable energy produced on-site, reducing the misused energy from 52.84% to 25.14%, as well as decreasing electricity costs by 58.46%.